Rice that Filipinos Grow and Eat - John C. de Leon (Philippine Institute for Development Studies (PIDS), 2005)
This paper introduces rice to the reader and analyzes the changes it has gone through these past 100 years in the shaping hands of varietal improvement science. Here, the richness of the crop as a genetic material and resource is revealed. Landrace rice, pureline selection rice, crossbred rice, semidwarf rice, hybrid rice, new plant type rice, designer rice - from the traditional to modern to futuristic - rice becomes all of these while traversing time in the Philippines. There is rice for the lowlands, uplands, the cool elevated; the irrigated and rainfed; the saline prone, drought prone, the flood prone - each kind serving as a wonderful display of dexterity from a tiny seed. Rice for full season farming and rice for double or relay cropping also exist. Of course, there must be rice for daily consumption and rice for important occasions. There is nonsticky rice or the glutinous opposite; well milled or brown rice; red rice; aromatic rice; micronutrient dense rice; golden rice; the generic fancy or specialty rices; even rice with healing wonders or medicinal properties. Harnessed by purposeful R&D, rice ably provides for the multiplicity of our needs. And though very much transformed already rice remains culture-friendly, like the science that does not tire molding it. Viewed in these sense, rice becomes very precious and unabandonable to many.
Keywords: 330; rice sector; rice culture; rice sufficiency; Filipinos; cultivated species; rice varieties; varietal improvement; yield; opportunities besides high yield; rice as essential food; rice as essential crop; Reis; Reisanbau; Philippinen